Education of Drug Side Effect And Improper Use of Drugs at Hasanudin Pandeglang Orphanage - Stiani, Sofi Nurmay; Yusransyah, Yusransyah; Ernawati, Eneng Elda; Udin, Baha; US, Sumarlin; Fahlevy, Muhamad Ichsan; Junaedi, Candra; Noviyanto, Fajrin (Jurnal IPTEK Bagi Masyarakat, 2025)
Improper use of drugs can cause adverse side effects, especially among people with limited access to information such as people living in orphanages. This community service activity aims to increase the knowledge of residents of the Hasanudin Pandeglang Orphanage regarding the side effects of drugs and the risks of incorrect drug use through educational activities. The method used is health education accompanied by a question and answer discussion and pretest and posttest evaluation using a knowledge questionnaire. The questionnaire was designed to measure participants’ understanding of the material presented before and after education. The number of participants in this activity was 57 participants. The evaluation results showed a significant increase in participants’ knowledge scores after the education. This proves that this educational activity is effective in increasing awareness and understanding of the safe use of drugs. This activity is expected to be a model for similar health education in other orphanages to prevent irrational drug use.